MEASUREMENT OF HEALTH LEVEL WITH APPROACH TO CAPITAL ADEQUACY LEVEL AND SATISFACTION LEVEL OF BANK FINANCING SUPPORT AT PT. GRESIK PETROCHEMICAL - Afrian, Fuguh Imami; Windijarto (Jurnal Ekonomi, 2022)
This study aims to determine the level of health by using a capital level measurement approach and to determine the level of satisfaction of the bank's financing support at PT. Gresik Petrochemicals. The data used in the study used primary data and secondary data. The primary data used are sourced from in-depth interviews with the Vice President of Finance, AVP of Treasury, fund management staff, and project administration at PT. Gresik Petrochemicals. As for the secondary data in this study, it was obtained from the annual financial report (annual report) that has been published by each bank through the Indonesian Financial Services Authority during the range of 2019 – 2020. The data analysis technique uses a soundness level measurement with a capital adequacy level (CAR) approach. and gap analysis. The results of the study show that aspects of the ease of the financing process, low service fees and low interest rates on loans provided by banks on the assurance dimension as well as aspects of bank reputation and account security on the reliability dimension are also aspects that are considered the most important for PT. Petrokimia Gresik in determining or selecting a bank as financing. The results of measuring the level of satisfaction expectations using gap analysis show that BNI, MUFG and Mandiri Banks have an average overall level of satisfaction with dimensions close to what is expected by PT. Petrokimia Gresik with a satisfaction level of more than 95 percent or 98.49 percent, 97.19 percent and 95.49 percent respectively. Until now PT. Petrokimia Gresik in choosing or determining which bank to use for financing is still focused or only considering the service aspect. Measurement of bank soundness level has not been taken into consideration by PT. Petrokimia Gresik in the selection of banks for financing. The results of this study indicate that all banks that have been providing financing facilities are categorized as very healthy with CAR values ​​above 12 percent. MUFG holds the largest CAR value with a value of 88.19 percent.